2021
DOI: 10.1021/acscatal.0c05454
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Single-Atom-Doped Ga2O3 Catalysts for Propane Dehydrogenation: Breaking through Volcano Plot by Lewis Acid–Base Interactions

Abstract: Volcano curves have proven to be particularly useful in new catalyst design in the field of heterogeneous catalysis. On the other hand, the further enhancement of the performance of the optimal catalyst for a given reaction is inherently limited by the Sabatier principle. In this work, microkinetic analysis has been carried out to examine the adsorption and catalytic behaviors of single-atom-doped Ga2O3 catalysts in propane dehydrogenation (PDH), which shows that the volcano-shaped activity plot can be broken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 60 publications
0
47
2
Order By: Relevance
“…The calculations indicated that Pt−O is likely to facilitate the C−H bond activation in propane, whereas Ga− O is responsible for H recombination. 34,35 However, these calculations postulated the atomically dispersed "cationic" Pt on the Ga 2 O 3 surface, which is different from the earlier experimental results indicating the formation of reduced Pt particles under PDH reaction conditions. 29,30 In the present study, the PDH reaction mechanism and catalytic interplay of Ga, Pt, and Ce on the γ-Al 2 O 3 surface are carefully investigated by combining various techniques, including selective poisoning experiments, in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), DFT calculations, and H 2 −D 2 isotope scrambling.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…The calculations indicated that Pt−O is likely to facilitate the C−H bond activation in propane, whereas Ga− O is responsible for H recombination. 34,35 However, these calculations postulated the atomically dispersed "cationic" Pt on the Ga 2 O 3 surface, which is different from the earlier experimental results indicating the formation of reduced Pt particles under PDH reaction conditions. 29,30 In the present study, the PDH reaction mechanism and catalytic interplay of Ga, Pt, and Ce on the γ-Al 2 O 3 surface are carefully investigated by combining various techniques, including selective poisoning experiments, in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), DFT calculations, and H 2 −D 2 isotope scrambling.…”
Section: Introductioncontrasting
confidence: 61%
“…Recently, density functional theory (DFT) calculations have been performed to understand the catalytic roles of Pt and Ga in Pt-doped Ga 2 O 3 . The calculations indicated that Pt–O is likely to facilitate the C–H bond activation in propane, whereas Ga–O is responsible for H recombination. , However, these calculations postulated the atomically dispersed “cationic” Pt on the Ga 2 O 3 surface, which is different from the earlier experimental results indicating the formation of reduced Pt particles under PDH reaction conditions. , …”
Section: Introductioncontrasting
confidence: 56%
“…The Pt−O site is more active than the Ga(o)-O site in the propane activation, having a lower activation energy of the rate-limiting step. However, further studies have demonstrated that the Ir 1 −Ga 2 O 3 catalyst is more effective than the Pt-doped Ga 2 O 3 catalyst in PDH reaction [32].…”
Section: Theoretical Studiesmentioning
confidence: 98%
“…8 Several kinds of materials (Al 2 O 3 , CeO 2 , ZrO 2 , Ga 2 O 3 , SiO 2 , MgAl 2 O 4 /ZnAl 2 O 4 , zeolite, and carbon materials) have been utilized as supports in heterogeneous catalysis of alkane dehydrogenation. [30][31][32][33][34][35][36][37][38] The categories of supports are simply classified as oxides and other materials.…”
Section: Pt-based Catalystsmentioning
confidence: 99%
“…37 Chang et al carried out a microscopic dynamic analysis of a single atom doped Ga 2 O 3 catalyst, achieving an important breakthrough with volcano-like plots, which can be attributed to the interaction originating from Lewis acid-base effects. 38 Deng and colleagues synthesized a precursor material through a wet impregnation method and then modified it with Pt nanoparticles, which acted as the major active center by a direct H 2 reduction pathway. 47 The authors claimed that the superior performance with a conversion of 21.3% and a selectivity of 94.4% is mainly attributed to the SMSI effect between the support and active center.…”
Section: Pt-based Catalystsmentioning
confidence: 99%